CAT 2024: Important Documents Required for CAP Interview Round

CAT General Equation of Circle - Practice Questions & MCQ

Edited By admin | Updated on Oct 04, 2023 04:20 PM | #CAT

Quick Facts

  • 5 Questions around this concept.

Solve by difficulty

The equation of the circle centred at the origin and having a radius of 6 units is:

Concepts Covered - 1

General Equation of Circle

Now, let's find the equation of of circle

Let P(x, y) be any point on the circumference of the circle with centre at C (h,k).

Then, by definition, | CP | = r. It means that the distance from the point C to point P is constant, which is radius r.

Using the distance formula, we have

\\\mathrm{\;\;\;\;\;\;\;\;\;\;\;\;\sqrt{(x-h)^{2}+(y-k)^{2}}=r}\\\\\mathrm{i.e.\;\;\;\;\;\;\;\;\;\;\;(x-h)^{2}+(y-k)^{2}=r^{2}}

If the centre of the circle is the origin or (0,0) (i.e h =0 and k = 0)

Then the equation of the circle becomes

\\\mathrm{\;\;\;\;\;\;\;\left (x-0 \right )^2+\left (y-0 \right )^2=r^2}\\\\\Rightarrow \mathrm{\quad\quad\quad\quad\;\;\;\;\;\; x^2+y^2=r^2}

In the previous concept, we learn that the equation of circle when center, C(h,k) and radius r given is \mathrm{ (x-h)^2+(y-k)^2=r^2}.

Now simplify this using the identity \mathrm{ \left ( a-b \right )^2=a^2-2ab+b^2}

\\\\\Rightarrow\mathrm{ (x-h)^2+(y-k)^2=r^2} \\\Rightarrow \mathrm{x^2-2hx+h^2+y^2-2yk+k^2=r^2}\\\Rightarrow\mathrm{ x^2+y^2-2hx-2ky+h^2+k^2-r^2=0}

Compare the above equation with  \mathrm{x^2+y^2+2gx+2fy+c=0 }

we get,

\begin{aligned} \mathrm{h}&=\mathrm{-g}\\\mathrm{k}&=\mathrm{-f}\\\mathrm{h^2+k^2-r^2}&=\mathrm{c}\\\text{or }\mathrm{h^2+k^2-c}&=\mathrm{r^2} \end{aligned}

Therefore the equation of any circle can be expressed in the form

\\\Rightarrow \mathrm{x^2+y^2+2gx+2fy+c=0}

This is known as the general equation of the circle.

Again,

\begin{aligned} &x^{2}+y^{2}+2 g x+2 f y+c=0\\ &\begin{array}{l} \Rightarrow\left(x^{2}+2 g x+g^{2}\right)+\left(y^{2}+2 f y+f^{2}\right)=g^{2}+f^{2}-c \\ \Rightarrow(x+g)^{2}+(y+f)^{2}=(\sqrt{g^{2}+f^{2}-c})^{2} \\ \Rightarrow\{x-(-g)\}^{2}+\{y-(-f)\}^{2}=(\sqrt{g^{2}+f^{2}-c})^{2} \end{array} \end{aligned}

This is of the form \mathrm{(x-h)^{2}+(y-k)^{2}=r^{2}} which represents a circle having centre at (- g, -f) and radius \mathrm{\sqrt{g^{2}+f^{2}-c}}.

Note that:

  1. If g2 + f2 - c = 0,  then the above equation represents a point circle.
  2. If g2 + f2 - c < 0,  then the above equation does not represent a circle.

"Stay in the loop. Receive exam news, study resources, and expert advice!"

Get Answer to all your questions

Back to top